Physiological Effects of Microbial Biocontrol Agents in the Maize Phyllosphere - María Fiamma Grossi Vanacore; Melina Sartori; Francisco Giordanino; Germán Barros; Andrea Nesci; Daiana García (Plants, 2023)
In a world with constant population growth, and in the context of climate change, the need to supply the demand of safe crops has stimulated an interest in ecological products that can increase agricultural productivity. This implies the use of beneficial organisms and natural products to improve crop performance and control pests and diseases, replacing chemical compounds that can affect the environment and human health. Microbial biological control agents (MBCAs) interact with pathogens directly or by inducing a physiological state of resistance in the plant. This involves several mechanisms, like interference with phytohormone pathways and priming defensive compounds. In Argentina, one of the world’s main maize exporters, yield is restricted by several limitations, including foliar diseases such as common rust and northern corn leaf blight (NCLB). Here, we discuss the impact of pathogen infection on important food crops and MBCA interactions with the plant’s immune system, and its biochemical indicators such as phytohormones, reactive oxygen species, phenolic compounds and lytic enzymes, focused mainly on the maize–NCLB pathosystem. MBCA could be integrated into disease management as a mechanism to improve the plant’s inducible defences against foliar diseases. However, there is still much to elucidate regarding plant responses when exposed to hemibiotrophic pathogens.